Quantum Fundamentalism and Theological Liberty - Harris, Mark (Zygon, 2024)
Quantum mechanics (QM) is astonishingly successful as a theoretical framework, underpinning countless scientific areas and providing the impetus behind entire technologies. Many scientists suspect that physical reality is fundamentally quantum in nature, even if we perceive little of this in our everyday human experience. This is the viewpoint of "quantum fundamentalism." Yet, the conceptual implications of QM defy common sense, to such an extent that popular culture largely perceives of QM as a source of counterintuitive weirdness. At the same time, bestselling self-help manuals portray QM as a source of hidden healing power within, while spiritual readings invoke QM as a bridge to the divine, or as a source of theological analogies. Scientists often denounce these mystical approaches as "quantum quackery," but I examine their serious side. I argue that, for quantum fundamentalism to function as a worldview, it should inform a sense of human purpose, something for which theological analysis is well equipped.